Wohnlich, Venice Biennial of architecture 2008: Exhibition and its geneses - Tomić-Vasiljević Dragana; Cvetić Mariela (Arhitektura i Urbanizam, 2009)
The procession from the response, that comes in the form of concept, to the entitled exposition theme, via the materialization of that concept in the given or chosen exposition area (technical representation), up to the exhibition realization leads over the numerous accompanying activities that include informative propaganda, the activities concerning the preview and publishing catalogue as an advertising, scientific and educative instrument of the exhibition. The intention of this work is to point at some segments of that general trajectory at the example of Serbian pavilion in Venice biennale of architecture 2008.